Abyssinone V-4' Methyl Ether Isolated from Erythrina droogmansiana (Leguminosae) Inhibits Cell Growth and Mammary Glands Hyperplasia Induced in Swiss Mice by the 7, 12-Dimethylbenz(a)anthracene. (11th July 2018) - Tueche, Alain Brice; Zingue, Stephane; Tchoupang, Edwige Nana; Gueyo, Telesphore Nanbo; Gbaweng Yaya, Abel Joël; Njuh, Amstrong Nang; Ntsa, Dieudonnée Mireille; Njamen, Dieudonné
Abstract : There is a long standing interest in the identification of medicinal plants and derived natural products for developing cancer therapeutics. The present study was designed to evaluate the in vitro and in vivo antiproliferative effects of Abyssinone V-4' methyl ether (AVME) on breast tissue of mice. The cytotoxicity of AVME was evaluated using MTT assay in four cancer cell lines (DU145, PC3, HepG2, and MCF-7). Further, a protective effect of AVME was evaluated on 7, 12-dimethylbenz(a)anthracene- (DMBA-) induced breast tumor in Swiss mice. Incidence, burden, volume, and histological analysis of mammary tumors were measured. As a result, AVME inhibits DU145, PC3, HepG2, and MCF-7 cells growth. In vivo, no tumor was detected in mice from the normal group as compared to those of DMBA group. Moreover, AVME inhibits the DMBA-induced mammary glands hyperplasia in mice at the dose of 10 mg/kg, evidenced by a decrease of tumor incidence, tumor weight, and volume as well as a protective effect against the lobular alveolar hyperplasia. Taken all together, these results suggest that Abyssinone V-4' methyl ether is endowed with antitumor properties and could be a source of traditional medicine which deserves to be more elucidated and explored in the foreseeable future.